India's Calorie Consumption Puzzle: Insights From the Stochastic Cost Frontier Analysis of Calorie Purchases - Gautam Hazarika; Sourabh Bikas Paul (Institute of Labor Economics (IZA), 2020)
Between the early 1970s and very nearly the present, Indians' per capita calorie consumption declined. This decline, perplexing in the face of rising per capita income when malnutrition is rampant, has been termed India's Calorie Consumption Puzzle. It has been partially attributed to a squeeze in the household food budget. This study employs Stochastic Cost Frontier Analysis to evaluate this explanation, upon the logic that such a squeeze shall likely result in the rising cost-efficiency of calorie purchases, that is, the more economical purchase of calories. Analysis of household expenditure data from India's National Sample Survey reveals that Indian households' purchase of calories did become more cost-efficient at every level of income, suggesting that there was indeed a squeeze in the household food budget, making this a viable explanation of the Calorie Consumption Puzzle. Besides thus investigating India's Calorie Consumption Puzzle, this study demonstrates a novel application of Stochastic Cost Frontier Analysis, to consumption instead of the more common production, in that the method has not previously been applied to the consumption of multiple items treated as inputs yielding an output. Stochastic Cost Frontier Analysis applied to calorie acquisition may be a new way of gauging changes over time in food security, with a rise in cost-efficiency indicating a squeeze in the food budget or declining food security.
Keywords: I32; O1; 330; calorie consumption puzzle; Stochastic Cost Frontier Analysis